“Mestizagem’ y ‘Transculturación” como políticas y prácticas de convivencia: Gilberto Freyre (Casa-grande & senzala, 1933) y Fernando Ortiz (Contrapunteo cubano del tabaco y del azúcar, 1940) - Nitschack, Horts (2016)
This article compares two classic texts on the plantation society: Casa-grande & senzala by the Brazilianauthor Gilberto Freyre and Contrapunteo cubano del tabaco y el azúcar (1940), by the CubanFernando Ortiz. The two authors describe and analyze the coexistence of groups and individuals ofdifferent ethical, cultural, and social origins with two concepts that signify profoundly different values:‘mestizaje’ or miscegenation (Gilberto Freyre) and ‘transcultural’ (Fernando Ortiz). With ‘mestizaje’the ‘myth of the three races’ is maintained. The basis of coexistence is ultimately biologicalmiscegenation under the conditions of the colonial society, the laws and order of which are not challengedby the process of miscegenation. The coexistence of mestizaje is marked by ambivalencebetween repression and protection. Fernando Ortiz’s ‘transculturation’ defines the subjects by theirsocial practices and their position in the economic and social power settings. As a consequence, itaddresses complex processes of empowerment and negotiation in which both the dominating subjectand the dominated are involved. Despite their differences, the two concepts make a significantcontribution to a reevaluation of Latin American cultures in comparison with Nordic cultures.